If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y = 3y + 18 Reorder the terms: 6y = 18 + 3y Solving 6y = 18 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 6y + -3y = 18 + 3y + -3y Combine like terms: 6y + -3y = 3y 3y = 18 + 3y + -3y Combine like terms: 3y + -3y = 0 3y = 18 + 0 3y = 18 Divide each side by '3'. y = 6 Simplifying y = 6
| .61+x=137.86 | | 7n=3n-52 | | 6xy-17=4xy+11 | | -16=-259+x | | 64x^2-144x+585=0 | | x/4-3=33 | | 9y=5-(y+6) | | -6(7x-8)=12 | | c+160=1850 | | n+7=8n | | -100=-7x-5(8+x) | | -0.7+1.15=-0.4x+1.75 | | 4y^2=12 | | (4m+5)2= | | 1.83/9 | | -31=x-54 | | 5x-7=2(3x-5) | | 4(t-3)+5t=t-3 | | 12x^2+33x-9=y | | 1.4x-4.8=0.6x-3.28 | | 750000+5+800000+3=1x | | 1.5x+2.7=0.8+0.95 | | 88-w=173 | | 3/(2x-3)=2/(x+5) | | 4x+1/7x=6 | | 750000+5x=800000+3x | | 4x-8+3x=12+6x | | y-26=-28 | | -6+3(-1-b)=19 | | (3x+6)+(3x)+(3x+5)=(3x)+(3x)+(4x+6) | | -3x+7=2y+9 | | 5+3(x-2)=-1 |